Plasma amino acid profiles in dogs with closed extrahepatic portosystemic shunts are only partially improved 3 months after successful gradual attenuation - Nausikaa Devriendt (Wiley, 2021)
Abstract Background Dogs with portosystemic shunts have an altered blood amino acid profile, with an abnormal branched‐chained amino acid (BCAA)‐to‐aromatic amino acid (AAA) ratio being the most common abnormality. Different liver diseases have distinctive amino acid profiles. Objectives Determine the changes in plasma amino acid profiles in dogs with extrahepatic portosystemic shunts (EHPSS) from diagnosis to complete closure. Animals Ten client‐owned dogs with EHPSS closed after surgical attenuation. Methods Prospective cohort study. Medical treatment was instituted in dogs diagnosed with EHPSS. At least 4 weeks later, gradual surgical attenuation was performed. Three months postoperatively, EHPSS closure was confirmed by transsplenic portal scintigraphy. Clinical signs were scored and blood was taken before institution of medical treatment, at time of surgery, and 3 months postoperatively. At the end of the study, the plasma amino acid profiles were analyzed in batch. Results The median BCAA‐to‐AAA ratio was extremely low (0.6) at time of diagnosis and remained low (0.5) at time of surgery, despite the fact that median neurological score significantly improved from 22 to 2 after starting medical treatment (P = .04). Three months after surgical attenuation, a significantly higher BCAA‐to‐AAA ratio (1.5) was observed (P < .001). Conclusions and Clinical Importance Medical treatment does not improve the BCAA‐to‐AAA ratio in dogs with EHPSS, despite substantial clinical improvement. Although the ratio significantly increased after EHPSS closure, it was still indicative of moderate to severe hepatic dysfunction in all dogs.